Treatment-Related Serious Adverse Events of Immune Checkpoint Inhibitors in Clinical Trials: A Systematic Review - Ouyang, Tao; Cao, Yanyan; Kan, Xuefeng; Chen, Lei; Ren, Yanqiao; Sun, Tao; Yan, Liangliang; Xiong, Bin; Liang, Bin; Zheng, Chuansheng (Frontiers in Oncology, 2021)
Background Immune Checkpoint Inhibitors (ICI) have been progressively used in cancer treatment and produced unique toxicity profiles. This systematic review aims to comprehend the patterns and occurrence of treatment-related adverse events (trAEs) based on ICI. Methods PICOS/PRISMA methods were used to identify published English-language on PubMed, Web of Science, and Scopus from 2015 to 2020. Published clinical trials on ICI monotherapy, combined ICIs, and ICI plus other treatment with tabulated data on grade≥3 trAEs were included. Odds ratio (OR), χ2 tests were used to analyze for effect size and associations. Results This review included 145 clinical trials involving 21786 patients. Grade 3-5 trAEs were more common with ICI when they were plused with other treatments compared with ICI monotherapy(54.3% versus 17.7%, 46.1%, p<0.05). Grade 3-5 trAEs were also more common with CTLA-4 mAbs compared with anti-PD-1 and anti-PD-L1 (34.2% versus 15.1%, 13.6%, p<0.05). Hyperthyroidism (OR 3.8, 95%CI 1.7–8.6), nausea (OR 3.7, 95%CI 2.5–5.3), diarrhea (OR 2.7, 95%CI 2.2–3.2), colitis (OR 3.4, 95%CI 2.7–4.3), ALT increase (OR 4.9, 95%CI 3.9–6.1), AST increase (OR 3.8, 95%CI 3.0–4.9), pruritus (OR 2.4, 95%CI 1.5–3.9), rash (OR 2.8, 95%CI 2.1–3.8), fatigue (OR 2.8, 95%CI 2.2–3.7), decreased appetite (OR 2.4, 95%CI 1.5–3.8), and hypophysitis (OR 2.0, 95%CI 1.2–3.3) were more frequent with combined ICIs. Diarrhea (OR 8.1, 95%CI 6.4–10.3), colitis (OR 12.2, 95%CI 8.7–17.1), ALT increase (OR 5.1, 95%CI 3.5–7.4), AST increase (OR 4.2, 95%CI 2.8–6.3), pruritus (OR 4.1, 95%CI 2.0–8.4), rash (OR 4.4, 95%CI 2.9–6.8), hypophysitis (OR 12.1, 95%CI 6.3–23.4) were more common with CTLA-4 mAbs; whereas pneumonitis (OR 4.7, 95% CI 2.1–10.3) were more frequent with PD-1 mAbs. Conclusions Different immune checkpoint inhibitors are associated with different treatment-related adverse events profiles. A comprehensive data in this systematic review will provide comprehensive information for clinicians.